(untitled) (Journal of Asian Development Studies, 2023)
This study explicates the choices of words used in the selected newspapers of national and international scope for constructing ideology and power relationships of three cricketing nations, i.e., India, Pakistan, and Australia. The study examines the ideological and power relations through vocabulary and textual choices. The study also investigates the discursive practices related to the discourse of cricket and highlights the salient features within the text/corpus of Pakistani and international newspapers. The study further explores the ideological underpinnings of the selected newspaper stories and unearths the author’s choices in lexical fields/items. The study is significant in many ways as it unfolds the pattern and method in which sports, specifically the game of cricket, have become the source of constructing ideology and power. The data for this study is gathered from stories from two newspapers, "Dawn" and "BBC." Foucauldian paradigm of power and Knowledge, disciplinary power, corpus-assisted Discourse analysis, and Thematic Analysis are used to analyze the data. The study is both qualitative and quantitative. The study’s data has brought forward that the game of cricket is presented through the media discourse carrying certain ideologies, power structures, and dominance of a particular cricket-playing nation over the other off the field.